2008
DOI: 10.1056/nejmoa0804328
|View full text |Cite
|
Sign up to set email alerts
|

GAD Treatment and Insulin Secretion in Recent-Onset Type 1 Diabetes

Abstract: GAD-alum may contribute to the preservation of residual insulin secretion in patients with recent-onset type 1 diabetes, although it did not change the insulin requirement. (ClinicalTrials.gov number, NCT00435981.)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
402
4
5

Year Published

2009
2009
2013
2013

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 465 publications
(430 citation statements)
references
References 28 publications
16
402
4
5
Order By: Relevance
“…A dose-finding study in Latent Autoimmune Diabetes in Adults (LADA) patients supported the clinical effect and safety of subcutaneous administration of 20 µg alum-formulated recombinant human GAD 65 (GADalum) [13], and the 5-year follow up suggests a persistent effect [14]. We have conducted a phase II clinical trial, where we showed that two injections of 20 µg GAD-alum contributes to the preservation of residual insulin secretion in children with recent onset type 1 diabetes [15].…”
Section: Introductionmentioning
confidence: 91%
“…A dose-finding study in Latent Autoimmune Diabetes in Adults (LADA) patients supported the clinical effect and safety of subcutaneous administration of 20 µg alum-formulated recombinant human GAD 65 (GADalum) [13], and the 5-year follow up suggests a persistent effect [14]. We have conducted a phase II clinical trial, where we showed that two injections of 20 µg GAD-alum contributes to the preservation of residual insulin secretion in children with recent onset type 1 diabetes [15].…”
Section: Introductionmentioning
confidence: 91%
“…While insulin autoimmunity is affecting the young, GAD65 autoimmunity is less sensitive to age. Alum-formulated recombinant human GAD65 tested in Phase II and III clinical trials were found to be safe [38][39][40] . The immunomodulating effect seemed to include the induction of Treg cells 16,38 and the residual beta-cell function in newly diagnosed T1D patients.…”
Section: Glutamic Acid Decarboxylase (Gad65)mentioning
confidence: 99%
“…GAD-alum tested in Phase II clinical trials with some effect on preserving residual cpeptide 39,40 was tested in an additional phase II trial with a dose-regiment that differed from previous trials 53 . Two or three doses of subcutaneous GAD-alum across 4-12 weeks did not alter the c-peptide disappearance rate during 12 month in newly diagnosed T1D patients (NCT00529399).…”
Section: Gad-alummentioning
confidence: 99%
See 2 more Smart Citations